A experiência educativa de uma casa familiar rural e suas contribuições para o desenvolvimento local - ALMADA, Francisco de Assis Carvalho de (2005)
The present work consists of a study about activities of the Rural Family House of Coquelândia - Imperatriz/MA. To identify the looked for evidences and the several social actors action involved in the process, the work alicerça-if, mainly, in the analysis of the functions carried out by the Rural Family House, considering that those actions possess a clear relationship with the sistematização of knowledge, that facilitate the social actors transformation in active agents in the actions of local development. Like this being, it is underlined the Pedagogy of the Alternation and its role in the construction of the local development, its practice in the revaluation multicultural of the field and its contribution in the social actors performance transformadora in building agents of its own history. For so much we made a rising of the history of the Alternation with emphasis in its model organizativo and in its pedagogic instruments. We observed that the practice of the Rural Family House of Coquelândia allows to the families not only the youths opportunity to reconcile the work activities and studies, but also, the parents direct participation in the educational process. It was also verified that through the relationship theory-practice the families notice the youths changes comportamentais and its motivations for the studies and, with that, they are impelled more and more to collaborate with the monitors. The formation for alternation constitutes in a factor of fundamental dimensions so that they are processed and consolidate the changes in the relationship with that new reality. It is ended that the Pedagogy of the Alternation collaborates with the formation of enterprising subjects with capacity and critical conscience for interaction and transformation in fact in that live.